2016
DOI: 10.1038/srep38337
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Self-Organized Dewetting of Ultrathin Polymer Blend Film for Large-Area Fabrication of SERS Substrate

Abstract: We study the enhanced dewetting of ultrathin Polystyrene (PS)/Poly (methyl methacrylate) (PMMA) blend films in a mixed solution, and reveal the dewetting can act as a simple and effective method to fabricate large-area surface-enhanced Raman scattering (SERS) substrate. A bilayer structure consisting of under PMMA layer and upper PS layer forms due to vertical phase separation of immiscible PS/PMMA during the spin-coating process. The thicker layer of the bilayer structure dominates the dewetting structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Nanostructured photonic devices have been developed for and utilized in various applications, including displays [ 18 ], lighting [ 19 , 20 ], solar cells [ 21 , 22 ], mechanical sensors [ 23 , 24 ], and biosensors [ 25 ]. The optical properties of photonic nanostructures depend heavily on their geometric parameters; consequently, they can be manipulated by changing the nanostructures’ designs [ 26 , 27 , 28 ]. Although photonic nanostructures can be optimized for and utilized in specific applications, on the downside, the predefined physical structures have a limited tuning capability and working bandwidth that could restrict potential applications [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured photonic devices have been developed for and utilized in various applications, including displays [ 18 ], lighting [ 19 , 20 ], solar cells [ 21 , 22 ], mechanical sensors [ 23 , 24 ], and biosensors [ 25 ]. The optical properties of photonic nanostructures depend heavily on their geometric parameters; consequently, they can be manipulated by changing the nanostructures’ designs [ 26 , 27 , 28 ]. Although photonic nanostructures can be optimized for and utilized in specific applications, on the downside, the predefined physical structures have a limited tuning capability and working bandwidth that could restrict potential applications [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Zhang et al and Bhandaru et al could utilize the dewetting of a polymer blend thin film for fabricating SERS substrates and antireflection coatings, respectively. 27,28 In this paper, we show yet another novel application of thin polystyrene (PS) film dewetting by using it as a sacrificial mask layer during the well-known hydrothermal growth of titania nanorods, which have been widely utilized in photocatalysis, 29 photoelectrochemical devices, 30 antireflective (AR) coatings, 31 self-cleaning, 32 microfluidic devices, 33 sensors, 34 and solid-state optoelectronic devices, 35 due to the oxidation efficiency, 36 biocompatibility, 37 and resistance to photocorrosion. 38 Interestingly, though hydrothermal growth of TiO 2 nanorod (NR) on a seeded FTO substrate is widely reported, barring very few papers, 39−42 almost every paper on the topic reports that the TiO 2 NR array is hydrophilic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lens-shaped microstructures on solid surfaces have numerous applications, such as surface antireflective coatings, bioimaging, data storage, optical lithography, ultraprecision positioning, , optothermal conversion, and surface-enhanced Raman scattering . Remarkably, recently it has been demonstrated that microlenses are able to overcome the diffraction limit and hence improve the resolution of optical imaging systems. Microlenses can be fabricated either individually or in batches.…”
Section: Introductionmentioning
confidence: 99%